The use of social media as a way of selling handicraft products from the baduy community. - Agus Prana Mulia (STIE Binaniaga, 2021)
Baduy Indigenous Community who live in Kanekes village, , as part of an isolated community that consistently carries out its ancestral traditions in farming (ngahuma) while maintaining harmony with nature, continues to experience a touch of online technology. Even though they do not have permission to use technology, as a result of the massive social interaction with outside visitors, the younger generation of Baduy are familiar with gadgets. The results of the research conducted in Baduy using analytical descriptive research methods found that the use of social media as a way of selling Baduy craft handicraft products has been very massive, since PT Telekomunikasi facilitated the Internet Training Center in 2016 which was followed by Community Access Points with an Internet network. Internet training in 2016 followed by a Community Access Point with an Internet network. The use of social media as a way of selling is not only done by Baduy people directly but also through the help of tour agents, freelance youtubers, bloggers and visitors who become sales agents by mouth selling in introducing handicrafts through the impression of SABA BADUY in social media.